Evaporation Analysis in Mushroom Cultivation Houses as an e-Module Supplementary Material to Enhance High School Students' Understanding of Physics Concepts - Fauziyah, Firda; Prihandono, Trapsilo; Subiki, Subiki (FKIP Universitas Lampung, 2022)
In majority, cultivation of oyster mushroom is carried out indoors, that the room was generally mentioned as mushroom cultivation house. One of physics concept that play a big role is evaporation. Evaporation itself known as a complex process that involves many physical quantities. It has been observed that in several schools in Jember, the explanations about evaporation, as one of discussion inside the unit of temperature and heat, were still non contextual and tended to be incomprehensible. This research aimed to describe the physics concept of evaporation that applied inside mushroom cultivation house, then design a supplementary e-module based the analysis as physics learning material. To measure the evaporation values that occur inside mushroom cultivation house, FAO-Penman Monteith evapotranspiration formula was chosen. For the supplementary e-module that has been designed, here is also validated by experts. Keywords: evaporation, mushroom cultivation house, oyster mushroom, and temperature and heat.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1493-1503